Increased productivity through SMED and TPM in a metalworking SME: an empirical investigation in the peruvian industry - Vargas Fiestas, Luigi Renzo (2025)
The objective of this study is to increase productivity and availability to improve profitability and competitiveness in the metal-mechanic sector. The case study is based on the implementation of TPM and SMED in an aluminum bolt production process in a Peruvian SME of the metal-mechanic sector where the current productivity is 9.23 units/manhour. SMED transforms internal activities by external ones in order to reduce the production cycle time. TPM autonomous/preventive makes it possible to apply a constant scheduled maintenance that improves and facilitates the activities performed by the machine in order to reduce operator effort and increase OEE. The implementation was validated through a pilot test that lasted 4 months where the results obtained were: 38.40% improvement in OEE, cycle time reduction from 6.51 minutes to 4.52 minutes, 16.93% increase in availability, MTBF increase from 12.5 to 22.43 hours/failure, MTTR reduction from 6.4 to 4.57 hours/failure, 30% performance improvement and productivity increase to 13.28 units/man-hour.